Implementation of Mass Cytometry as a Tool for Mechanism of Action Studies in Inflammatory Bowel Disease. Issue 11 (8th June 2018) - Tyler, Christopher J; Pérez-Jeldres, Tamara; Ehinger, Erik; Capaldo, Brian; Karuppuchamy, Thangaraj; Boyer, Joshua D; Patel, Derek; Dulai, Parambir; Boland, Brigid S; Lannigan, Joanne; Eckmann, Lars; Ernst, Peter B; et al.
Abstract: Background: Novel therapeutics for inflammatory bowel disease (IBD) are under development, yet mechanistic readouts at the tissue level are lacking. Techniques to assess intestinal immune composition could represent a valuable tool for mechanism of action (MOA) studies of novel drugs. Mass cytometry enables analysis of intestinal inflammatory cell infiltrate and corresponding molecular fingerprints with unprecedented resolution. Here, we aimed to optimize the methodology for isolation and cryopreservation of cells from intestinal tissue to allow for the potential implementation of mass cytometry in MOA studies. Methods: We investigated key technical issues, including minimal tissue requirements, cell isolation protocols, and cell storage, using intestinal biopsies and peripheral blood from healthy individuals. High-dimensional mass cytometry was employed for the analyses of biopsy-derived intestinal cellular subsets. Results: Dithiothreitol and mechanical dissociation decreased epithelial cell contamination and allowed for isolation of adequate cell numbers from 2 to 4 colonic or ileal biopsies (6 × 10 4 ±2 × 10 4 ) after a 20-minute collagenase digestion, allowing for reliable detection of most major immune cell subsets. Biopsies and antibody-labeled mononuclear cells could be cryopreserved for later processing and acquisition (viability > 70%; P < 0.05). Conclusions: Mass cytometry represents a unique tool for deep immunophenotyping intestinal cell composition. This technique has the potential to facilitate analysis of drug actions at the target tissue by identifying specific cellular subsets and their molecular signatures. Its widespread implementation may impact not only IBD research but also other gastrointestinal conditions where inflammatory cells play a role in pathogenesis.